Unearthing entrepreneurial opportunities among youth vendors and hawkers: Challenges and strategies - Isaac Kofi Biney (Journal of Innovation and Entrepreneurship, 2019)
This paper explores entrepreneurial opportunities among youth engaged in vending and hawking on the streets of Accra, Ghana. It ascertains challenges faced and strategies adopted to address them. Street vending and hawking is assuming increasing dimension due to paucity of formal job opportunities in Ghana. Hawking and vending of newspapers, textbooks, toffees and fruits are informal entrepreneurship opportunities on our streets. The study sought for short to medium and long-term plans the youth have to innovate the entrepreneurial opportunities in trades engaged in. It used youth hawkers operating at Okponglo and Dzorwulu junctions. Fifteen (15) youth participated in the study. It is a qualitative study which adopted purposive and convenience sampling procedures in selecting the sample. Thematic, analytical, descriptive-narrative interpretivist approaches were adopted in presenting the results. Crossing roads, chasing moving vehicles, operating in the scorching sun and torrential rain impacted negatively their health. It also emerged that the youth have plans to innovate and grow businesses, but the high cost of credit is a barrier. Lack of collateral for credits came up. Government quasi-financial institutions and non-bank financial institutions should be proactive in providing financial, advisory and technical support to the youth to exploit entrepreneurial opportunities in Ghana.
Keywords: 650; Entrepreneurial opportunities; Youth vendors and hawkers; Innovation; Financial support